Saluran Pemasaran Tanaman Hias di CV. Djuffal Florist Kecamatan Bumiaji Kota Batu - Rohmawan, Moch; Lidyana, Novita (Agrotechbiz : Jurnal Ilmiah Pertanian, 2022)
Marketing is the activity of channeling products from producers to consumers in various ways such as marketing channels. In Indonesia the need for ornamental plants or the demand for ornamental plants is increasing. The purpose of this study is to find out the Marketing channels carried out by CV Djuffal Floris. The analysis method used in this study is a qualitative method. CV. Djuffal Floris is engaged in the production and supplier of ornamental plants in Batu City. Types of ornamental plants produced CV. Djuffal Florist of Batu City include flowers and cut leaves such as Gerbera flowers, Carnations, Leather Leaf leaves and Ruskus. Marketing channels on CV. Djuffal Florist uses the form of direct and indirect channels. Because of CV. Djuffal Florist concurrently serves as a Farmer as well as a Supplier. As a CV Farmer. Djuffal Florist produces Ornamental plants. Such ornamental plants are sold to suppliers and sold to direct consumers. As a CV Supplier. Djuffal Florist also buys to farmers and other suppliers to distribute to consumers in need.Keywords : Marketing Channels; houseplants